POLISH SOCIETY «SOKІL» IN HALYCH (1903–1939) - KOZELKIVSKYI, Volodymyr (Halych. Scientific work collection, 2024)
The article examines the activities of the Polish society «Sokil» in Halych 1903–1939. The question of the number of members of the Halician nest has been studied. A brief historical description of the «Sokіl» building as one of the main centers of the cultural and gymnastic movement in the city was also made.